(untitled) (Journal of the College of Basic Education, 2025)
The present research aims to find out the effect of counseling program using some positive psychology techniques to develop gratitude of university students by testing the following hypothesis (there are no statistically significant differences between the grade levels of the experimental group and the control group on the gratitude scale in the pre- and post-tests at a significance level of 0.05). The researcher adopted the gratitude scale by (Hassan & Hussein , 2020). The validity of the translation was administrated, then the researcher extracted the statistical characteristics of the scale. It was concluded that all items of the scale have a statistically significant differences and correlation. The validity and reliability of the scale were approved as the reliability coefficient by the test and retest method was (0.87), and the reliability value by the Cronbach’s alpha method was (0.85). The scale consisted of (28) items. The researcher designed and applied a counseling program on a sample of (10) students as an experimental group. After applying the results, the researcher found that there were statistically significant differences between the grade levels of the experimental group scale in the pre- and post-tests , But there were no statistically significant differences between the grade levels of the control group in the pre- and post-tests, the researcher presented a number of conclusions, recommendations and proposals.